Analyzing the Relationship between Temperature, Precipitation and Burned Area: A case study from Churia-Siwalik, Nepal - Poudel, Kiran; Basnet, Rakshya (FORESTRY: Journal of Institute of Forestry, Nepal, 2024)
Forest fires are a major hazard, causing significant ecological, economic, and social damage worldwide. In Nepal, particularly in the Churia-Siwalik region, they are a recurring issue, exacerbated by climate change. This study examines the trends and associations between forest fires, climate, and weather patterns in the Churia-Siwalik region over the past two decades. We analyze the trends in burned areas, temperature, and precipitation from 2001 to 2024 using data from MODIS (MCD64A1) on burned areas and climate data on precipitation and temperature from USGS Earth Explorer. The results show a significant increasing trend in burned areas, with an average rise of 51.27 km² per year, reflecting growing wildfire risks. Temperature trends show a significant rise in temperature, and precipitation trends suggest a slight but statistically insignificant decline. The correlation analysis reveals a weak inverse relationship between precipitation and burned areas (r = -0.048, p = 0.82), while temperature shows a moderately positive correlation with burned areas (r = 0.42, p = 0.039). These findings underscore the critical role of climate variables in influencing the frequency and severity of wildfires in the Churia-Siwalik region and highlight the need for improved fire management strategies.